Educational Injustice in Sampek Engtay Drama by Nano Riantiarno - Waluyo, Budi; Lestari, Winda Dwi (International Journal of Multidisciplinary Sciences, 2025)
Education plays a very important and strategic role in shaping human resources that are productive, innovative, and have personalities under cultural values. In addition to providing cognitive, affective, and psychomotor values to every citizen, education is also used as a tool to transform values that are expected to be beneficial in the life of society, nation, and state [5]. Gender bias is favoring one gender in social life or public policy. Gender bias in education is an educational reality that favors one particular gender, which causes gender inequality. Various forms of gender inequality that occur in various fields of community life are also represented in the world of education. Educational processes and institutions are seen as playing a major role in socializing and preserving the values and perspectives that underlie the emergence of various gender inequalities in society. The concept of education often appears in literary works. One form of literature that contains about education is drama. Drama is a record of everyday events that are projected onto the stage. In line with that [1] mention that Learning in drama is process-oriented, a state of change that occurs in time and space, which happens within double frames of reality and fiction. Drama learning is process-oriented, with changes in time and space, which frame real and fantasy events. Drama is no different from other literary works, such as novels or short stories. It contains certain issues that the author wants to convey to the reader or audience. The object will be studied by the researchers is Nano Riantiarno's Sampek Engtay, a feminist drama or a drama that talks about women. This drama is very thick with the nuances of feminist criticism, namely the marginalization of education. This research is a qualitative descriptive study. In this research, qualitative information is described carefully and analytically. The description includes forms of criticism of the unfair treatment received by women in the field of education. The approach used in this research is feminism. This approach is used in order to interpret the deep meaning of the literary works studied in relation to people's lives. This is taken based on the assumption that basically literary works are the embodiment of people's lives. Thus the interpretation of the meaning in this literary work is a manifestation of that society.